The Components of Public Expenditures - عبد القادر بان صلاح (Journal of Legal Sciences, 2019)
The State shall comply with the requirements of its members and their general, it cannot be without the state spending Multiple expenses and images formats Affect the interests of society, but it should not ignore the administration This spending must be surrounded by all legitimate formulas and methods, approved by the legislature, according to the regulations and specific instructions, counting the expenditure is illegal and contrary to laws and regulations the executive branch has assumed responsibility and liability has legal consequences. In addition, spending must be properly, and corresponds to the economic situation of the country, achieve maximum benefit to all members of society, and not waste public funds in addition to the prior consent of the legislature to this expenditure.